Evaluation of design provisions on moment redistribution of composite partially encased continuous beams - Tan, Si Ming (Nanyang Technological University, 2022)
In this paper, a finite element analysis software DIANA is used to conduct a parametric study that focuses on the influence of parameters on moment redistribution of continuous partially encased composite beams. Composite beams have increasingly been adopted in the industry due to their advantages. It has a higher load-bearing capacity and longer spans can be achieved using composite beams, compared to when using conventional reinforced concrete beams. To exemplify these advantages, composite beams are often made continuous, with moment redistribution considered. Moment redistribution refers to the transfer of moments in statically indeterminate structures due to plastic reserve capacity. With moment redistribution considered, designs can be made more economical. However, there is still a lack of understanding of moment redistribution in encased composite beams and there is hardly any past study that focuses on this topic. Therefore, the parametric study conducted in this paper was to explore the parameters that could potentially affect moment redistribution in partially encased composite beams. ASIC 360 and EC4 both provided for the limits of the moment redistribution ratio. However, the specifications of the limits provided were too vague and generalized whereby the limits specified for non-encased conventional composite beams were used to apply to partially encased composite beams as well. Therefore, in this study, after obtaining results from the parametric study, the appropriateness of these provisions in both design codes was also evaluated. The results from this study imply that the parameters investigated do affect moment redistribution and yet they are not reflected in the provisions of the design codes. Although EC4 has clearer provisions with more factors considered, the limits provided in the design codes seem to be less conservative as compared to AISC-360. Given the current variations in the limits provided, both design codes were found to be unconservative. The large range of results obtained suggests that to improve the provisions of these codes, the limits provided should be varied according to factors that affect moment redistribution.